Stanislavsky’s Method and The Problems Encountered in Acting Education - Shamsiddin Usmonov (Art Time)
It is known that the universities of art and culture use art schools with their own style to supply competent, competent and competitive personnel to the art and culture institutions of our country. Education of young artists on the basis of the art school, which has proven itself through long-term research, is the basis for the development of mature specialists in the future. For this purpose, professors and pedagogues of art universities have developed their own instructional manuals, and these methods and manuals are subject to a certain art school.Every pedagogue in art schools has had his own style and directions since time immemorial. Regardless of the fact that each of these styles manifests itself in different forms, all of them are fed by the system devoted to the skills of the acting school, the art school in general, which was unified by K. S. Stanislavsky at the beginning of the last century.The organic process of behavior learned in the first course takes place in a complex environment, which requires a high level of technique from the student. Therefore, the training process in the acting workshop should be focused on deepening and strengthening previously acquired knowledge on the one hand, and mastering new elements of acting technique on the other hand.In particular, we can witness the use of beautiful decorations in the exam presented for the first semester of the second year. Or we can see students wearing make-up, using theatrical costumes. It is completely wrong to show a student who is just being formed with such a beautiful and healthy costume, make-up, and decorations, and we cannot see the student on the stage at all. We can't even find a budding actor on stage, let alone give enough credit to student actors. Because we are witnessing that the pedagogue covers the student actor with costumes, make-up, and decorations.